Membingkai Harmoni Alam: Ecoprint Sebagai Katalis Pemberdayaan Ekonomi Kreatif di Desa Turi - Tri Winarsih; Bayu Malikhul Askhar; Qosim, Qosim; Mesra Berlyn Hakim; Imtinan Widhah Kumala (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service is here to open new opportunities for the PKK mothers of Turi Village through Ecoprint Training. Amidst the challenges of limited income choices and abundant natural resources in the village, ecoprint has emerged as an innovative solution that is in line with the increasing market demand for environmentally friendly products. Recent data shows significant growth in Indonesia's sustainable fashion sector, but the spread of ecoprint knowledge still needs to be improved in rural areas. The main goal of this program is simple: to hone the technical skills of mothers in making ecoprints and open additional income for their families. We use a very practical approach, involving them directly from the preparation of gauze, arranging leaves, to the steaming and finishing process. We hope that through this program, ecoprint products from Turi Village will not only be a source of pride, but also improve the economic welfare of the community in a sustainable manner. In the future, we recommend the formation of business groups, facilitation of market access, design development, advanced training, and partnerships with the village government so that Turi ecoprint can continue to grow and become an icon of the creative economy